Thinking Relationally and Pedagogically about Commemoration: A Critical Inquiry into Charlottetown’s Macdonald Statue - Johnson, Kay (International Journal for Talent Development and Creativity, 2022)
In this article, I provide a critical reading of the now-removed statue of Sir John A. Macdonald in Charlottetown, Prince Edward Island, Canada. I bring together my own experience visiting the statue with understandings from Indigenous scholarship and public pedagogy theorizing to think about commemorations as public pedagogies that are foremost relational. I consider how the Macdonald statue works narratively, discursively, and as a site of embodied encounter to create a harmful relationality. Thinking relationally, and pedagogically, about colonial statues suggests possibilities not only for understanding how these commemorative practices produce bad relations but also for envisioning and enacting good relations.